Underwriting policy and its impact on the productivity of the life insurance portfolio: Analytical study in the "Iraqi General Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to study the basic concepts of the underwriting policy with its various indicators. The researcher studies the underwriting policy with its various indicators (sex, health status, age of the insured, insurance amount, The method of acceptance, payment method, and duration of insurance) where each of these indicators constitute an important factor in the productivity of life insurance policies, where the productivity of life insurance policies face many difficulties because insurance is a service and not a tangible material commodity and its benefits and not current. Therefore, the life insurance company needs to use a prudent underwriting policy so as not to endanger its financial position due to the expansion of the underwriting. In line with the research problem, which stipulates the weakness of the underwriting policy, which does not fit in the details of the insurance company and the research sample, as well as the dependence of employees in the issuance department in examining the applications of life insurance received for their company with a view to accepting, rejecting or postponing their coverage, on the accumulated experience. They have without taking into account the economic, social and political changes of the claimants. Accordingly, we will formulate the following question: What is the impact of the underwriting policy on the productivity of life insurance policies? The research hypothesis has been formulated to study and analyze the relationship between the underwriting policy and the life insurance policy of the insurance company. The research sample was determined by the Iraqi General Insurance Company.The statistical program SPSS-Ver (20) was used to extract the subscription policy for the period (2008-2017) as well as the use of the productivity of life insurance policies. The most prominent results of the research indicate that there is a strong and positive correlation between the underwriting policy and the productivity of life insurance policies. In general, the results of a simple impact analysis indicate that there is an impact between the underwriting policy and the productivity of life insurance policies.